Impact of median lobe on urinary function after robotic prostatectomy. Issue 12 (14th June 2021) - Martinez, Oscar; Murphy, Christopher; Bsatee, Aya; Abaza, Ronney
Abstract: Background: Enlarged median lobes (ML) can be technically challenging, particularly during bladder‐neck dissection, and may affect urinary functional outcomes of robotic radical prostatectomy (RARP). If known, the impact of potentially larger bladder necks on continence and chronic obstruction on postoperative urinary symptoms might aid patient counseling. We assessed the impact of intraoperatively identified median lobes (ML) on urinary function. Methods: We reviewed our prospective RP database from 2013 to 2020. AUA symptoms scores (AUA‐SS) were assessed preoperatively and at 1, 3, and 6 months. We compared patients with and without ML (NoML). Bladder‐neck sparing was routine to avoid reconstruction. Results: Of 663 patients who completed AUA‐SS questionnaires at all time points, 202 (30%) had ML. There were no significant differences in demographics, PSA, or clinical stage. Only two patients in ML and one in NoML group required bladder‐neck reconstruction (1.2% and 0.2%). There was no immediate or long‐term difference in continence rates between groups. Baseline mean AUA‐SS was higher in ML patients and showed more improvement postoperatively (−5.5 vs. −3.6, p < .05) with greatest improvement in ML patients with severe preoperative symptoms (−15.1). There was no difference in AUA‐SS between groups by 6 months. Conclusions: The presence of enlarged ML does not increase the risk of incontinence after RARP and it appears that ML patients have greater improvements in postsurgical urinary functions. Preoperative diagnosis of ML and lower urinary tract symptoms assessment could be helpful in counseling patients undergoing RARP regarding their expected postoperative urinary outcomes.